Feasibility of Additional Wastewater Treatment Plants for Water Quality Improvement at Nong Han Lake, Sakon Nakhon, Thailand - Chuaychoo, Pluem; Proysurin, Natthapong (International Journal of Biosciences and Biotechnology, 2023)
This study examined the possibility of additional wastewater treatment plants for the Nong Han Lake, Sakon Nakhon, Thailand. Hybrid constructed wetlands with horizontal and vertical flows (HFCW and VFCW) were selected for efficient nutrient removal, ease of operation and maintenance, and provision of recreational open space. The design is approximately 70,000 m2 (7 ha)—a decision made considering land availability for stabilization ponds where municipal wastewater carried through pipelines or sewerage accumulates, constructed wetland cells, and pumping stations. In HFCW and VFCW, nutrients are removed by the mechanisms of plant uptake and microbial metabolism. Results showed that HFCW reduced organic compounds, such as biochemical oxygen demand (BOD), by more than 90%, and VFCW removed at least 70% of nitrogen from wastewater. In addition, substantial reductions of up to 95% and 80% were obtained for total suspended solids (TSS) and phosphorus, respectively.